Palliative Gastrectomy Plus Chemotherapy versus Chemotherapy Alone for Incurable Advanced Gastric Cancer: A Meta-Analysis [Corrigendum] - Wu P; Wang PL; Ma B; Yin SC; Tan YE; Hou WB; Wang ZN; Xu HM; Zhu Z (Cancer Management and Research, 2024)
Wu P, Wang PL, Ma B, et al. Cancer Manag Res. 2018;10:4759–4771. The authors wish to advise that the published version of this article contains spelling errors. The text “randomixed control trail” in Figure 1 on page 4761, should read “randomized control trial”. The word “Beggar’s” used in the Publication bias section, line two, on page 4764 and for the caption of Figure 10, on Page 4767, should read “Begg’s”. The authors apologize for any confusion this may have caused. The journal wishes to advise readers that they have investigated the concerns for this article as indicated in the previously published Expression of Concern. The authors have now addressed these concerns and there are no further issues regarding the integrity of the article.